Immigration as practice of organization: discussions about practices of organization, displacement, and integration of Haitian immigrants in the Goiânia Metropolitan Region, in Goiás, Brazil - GABRIEL DO CARMO YAMAMOTO; JOSIANE SILVA DE OLIVEIRA (Cadernos EBAPE.BR, 2021)
Abstract This study aims to discuss the practices of displacement and organization that are part of the process of integrating Haitian immigrants in the countries that they live, in their diaspora process. Haiti is a country historically marked by displacement, which is observed since the colonial period, when people were forcibly displaced to be enslaved. This article will focus on the process of displacement, through the theoretical lens of Practice-Based Studies, using Michel de Certeau’s theory about social practices, associated with the concepts of Tim Cresswell about displacement and immigration as practice. The research was conducted between August and December 2017 in two Haitian communities in the Goiânia Metropolitan Region, in the state of Goiás, located in Central-West Brazil. For the production of empirical material, we used the techniques of life history interview and participant observation, by accompanying the everyday life activities in the immigrant’s communities. The results show that the practice of displacement of Haitian immigrants is an unfinished and still in process phenomenon, involving different dimensions of events, with international, national, and commuting displacement. It was also possible to conclude that the displacement practices are permeated by organizational practices and that “organizing” and “migrating” are processes involved. In addition, the practice of organization is a key component for integration and access to the workplace in Brazil. Therefore, immigration can be considered sets of practices to organize mobility experiences that are spatially multi-localized and incorporated.